Globalisation and neoliberalism as structural drivers of health inequities - Rama V. Baru; Malu Mohan (BMC, 2018)
Abstract In this paper, we draw upon and build on three presentations which were part of the plenary session on 'Structural Drivers of Health Inequities' at the National Conference on Health Inequities in India: Transformative Research for Action, organised by the Achutha Menon Centre for Health Science Studies in Trivandrum, India. The three presentations discussed the influential role played by globalisation and neoliberalism in shaping economic, social and political relationships across developed and developing countries. The paper further argues that the twin process of globalisation and liberalisation have been important drivers of health inequities. The first segment of the paper attempts a broader conceptualisation of neoliberalism beyond the economic realm. Using Stephanie Lee Mudge's conceptualisation (Soc Econ Rev 6:703-3, 2008) we have analysed how the political, bureaucratic and intellectual domains of neoliberalism have intersected and redefined the role of state and commercialised health services leading to inequities. Neoliberal ideas have reconfigured the role and changed the priorities of non-governmental organisations resulting in a fracture within this movement. n the second segment, we focus on the rise of American philanthro-capitalism, and how the two major foundations, the Rockefeller Foundation (early twentieth century) and the Bill and Melinda Gates Foundation (twenty-first century), have shaped the ideology of institutions engaged in international health and influenced the global health agenda. We discuss how the activities of philanthro-capitalists have transformed the architecture of health governance through their top-down organisational culture and deficit of structures to ensure accountability. The third and final segment of the paper focuses on how neoliberalism as a political project and cultural movement has forged alliances with conservative politics and religious fundamentalisms, resulting in negative consequences for women and other marginalised groups. These alliances have resulted in the control of women's bodies and contributed to the reversal of hard-won rights for health and gender justice in many parts of the world.